Ocular side effects of disopyramide. Issue 12 (December 1984) - Frucht, J; Freimann, I; Merin, S
Abstract : A patient who suffered from severe decrease of accommodation and pupillary dilatation following the systemic use of disopyramide is described. The ocular side effects when this drug is used in large doses result from its anticholinergic action.